Provision of Fitoimun® in Feed for the Growth and Survival of White Snapper (Lates calcarifer) Raised in Silvofishery Ponds in Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
This study aims to analyze the effect of adding Fitoimun® as a natural medicine on barramundi/white snapper (Lates calcarifer). Maintenance is carried out for 30 days, white snapper fry measuring 72-103 g with floating net cage containers measuring 4x4 m2 with a stocking density of 14 heads / repeats. The method used in this study was using Complete Randomized Design (RAL) with 3 treatments 3 replications with doses P0: 0 mL/kg feed, P1: 20 mL/kg feed, P2: 24 mL/kg feed. Parameters observed include survival, absolute weight growth, specific growth rate, and feed conversion ratio. The results obtained from the study showed that the administration of Fitoimun® had no real effect, although the application of Fitoimun® dose of 20 mL/kg feed had a survival rate of 100%, absolute weight growth of 78.7g, a specific growth rate of 2.1%, and the best feed conversion ratio of 1.63 than other doses.
Keywords: Fitoimun®; Growth; Lates calcarifer; Survival rate